(untitled) (The International Journal for Scientific Research, 2023)
The study aimed to identify the critical term for literary thoughts, especially those mentioned in ancient and modern Arabic literature. Literary thoughts are considered one of the literary arts, in which the Arabs toured and wrote many thoughts that reflect the breadth of their culture and their knowledge of the various arts and various fields of knowledge. Literary thoughts are special forms of expression that convey our thoughts and feelings to others. These thoughts were an important tributary of Arabic thought as they reflected on several topics. The study used the descriptive analytical method. The results of the study revealed that the art of thoughts is intertwined with many literary arts, and deals with special topics that are evident in the resources of personal and emotional experience. The study also recommended conducting further research to develop creative skills of writing thoughts.